Occupations after WWII: The Legacy of Rosie the Riveter - Andriana Bellou; Emanuela Cardia (Institute for the Study of Labor (IZA), 2013)
WWII induced a dramatic increase in female labor supply, which persisted over time, particularly for women with higher education. Using Census micro data we study the qualitative aspects of this long term increase through the lenses of the occupations women held after the war. Almost two decades after its end, we find that WWII had lasting, albeit complex but interesting effects on the occupational landscape. It led to a significant increase in the presence of young women, who were of working age at the time of the war, in manufacturing and professional/managerial occupations, while it entailed a decrease in the presence of older cohorts in clerical. Though differently, the effects surprisingly extended to the next generation of women who were too young to be working at the time of the war. For this cohort, the increase was concentrated in clerical and manufacturing. The entry of this very young cohort in clerical jobs and the exit of the older, suggests within-gender crowding-out; the increased presence of both cohorts in manufacturing, that the legacy of the wartime Rosies permeated occupational choices.
Keywords: J24; J31; N42; 330; WWII; occupations